The role of a woman in Tatar cultural traditions revival - Irina Kondrateva, Adelya Sattarova, Diana Sabirova, (Opción, 2019)
The aim of the paper is an immersion into national, secular and intra-confessional specifics of the cultural life of Tatar-Muslim women's community. The methodological basis was made by the system and structural, historical, anthropological and functional approaches. In result, activists of the Muslim movement, now, using cultural traditions and innovative approach solve the problem of ensuring communication between generations. In conclusion, developing of culture during the last decades in the republic of Tatarstan determines the content of the process of ethno-cultural traditions revival of the Tatar people, introducing a role of a female factor in sociocultural development of Tatarstan in general.